Teamwork in civil engineering -past, present, and future - Marlene Clarissa, Thomas Likup. (Universiti Malaysia Sarawak (UNIMAS), 2006)
This study is about the past, present and future teamwork in the civil engineering field. Since the topic of this study is very broad, the study will cover on organization structures, teamwork, and Team Development Model (TDM). In the research on the past organization structure of any civil engineering firm, it is found that majority practiced functional organization, whereas now, more and more matrix organization is practiced in the civil engineering organization structure. Nevertheless, in the past, the organization structure had more flaws than the current organization structure, and will keep on improving. The future organization structure is predicted to be either in a projectized form or still in a matrix form. Meanwhile, the teamwork in the past is found to be not as effective as the current teamwork practiced in the civil engineering industry. In the future, it is anticipated that teamwork could be getting better and will be done virtually at any time, any place and on any challenge. The met hod used for my research is by doing background studies, SWOT analysis, then coming out with results, discussion, recommendation and conclusion. Next, my research on the TDM showed that this general model does not necessarily help in improving the team’s performance therefore another TDM is developed to cater for the slight imperfections of the general model. With the help of the new TDM, it should be able to assist the team in attaining the optimum teamwork in the civil engineering world.